Novel uroflow stop test at time of catheter removal is a strong predictor of early urinary continence recovery following robotic‐assisted radical prostatectomy: A pilot study. Issue 1 (27th August 2013) - El‐Hakim, Assaad; Al‐Hathal, Naif; Al‐Qaoud, Talal; Gagné, Ginette; Larocque, Suzanne; Denis, Ronald; Zorn, Kevin C.
ABSTRACT Aim To study whether the ability to completely stop urinary flow during voiding at time of catheter removal, measured objectively using uroflowmetry, can predict early recovery of urine continence following robotic‐assisted radical prostatectomy (RARP). Materials and Methods In this pilot study, 108 patients with a minimum of 2 years follow‐up, operated by a single surgeon (AEH) were subjected to an uroflowmetry at the time of urethral catheter removal following RARP. Normal Saline (150 ml) was instilled intravesically prior to catheter removal and patients were instructed to attempt to stop urine flow during voiding in uroflowmeter. Two groups were studied, group one with positive Stop Test (n = 80) and group two with negative Stop Test (n = 28). Covariates included age, BMI, IPSS score, PSA, tumor stage, prostate volume, nerve sparing status, and estimated blood loss. Results Basic characteristics were not statistically different between both groups. Early continence recovery was significantly higher in group one. Pad‐free continence rates in group one and two at 1, 3, 6, 12, 18, and 24 months were 62% vs. 7% (P < 0.001), 85% vs. 28% (P < 0.001), 93% vs. 67% (P 0.001), 93% vs. 82% (P 0.079), 97% vs. 82% (P 0.006), and 97% vs. 85% (P 0.023), respectively. Uroflow Stop Test was the only independent predictor of early urine continence recovery on univariate and multivariate regression analysis [OR 2.87 (95%CI 1.34–4.38, P = < 0.001)]. Conclusion Novel use of uroflowmetry at time of urethral catheter removal is a simple, non‐invasive study with independent ability to predict early continence recovery following RARP. Neurourol. Urodynam. 34:60–64, 2015. © 2013 Wiley Periodicals, Inc.